Testing and simulation of 3D effects on progressive collapse resistance of RC buildings - Qian, Kai (2014)
This paper evaluates the three-dimensional (3D) or slab effects on reinforced concrete (RC) buildings to mitigate progressive collapse, which is caused by the loss of an interior column. Six one-quarter scaled beam–column, or beam–column–slab substructures are tested. These six specimens are categorised into three series (P-, T- and S-series). The test results confirm that transverse beams and RC slabs can reduce the collapse vulnerability of RC buildings effectively. In addition, it is quantified that 3D effects without slab can increase the yield load of the frame by up to 100%, while 3D effects including slab can increase the yield load up by 246.2%. This is because the slabs not only increase the bending moment capacity of beam sections working as flanges, but also provide more alternative load paths for load redistribution. RC slab can upgrade the first peak load of the buildings by developing compressive membrane actions, and upgrade the ultimate load capacity of the building during the large deformation stage by developing a tensile membrane action. As the number of tested specimens is relatively small, a series of numerical and parametric studies are carried out to further quantify the 3D or slab effects on RC buildings in resisting progressive collapse.